Инвариантные множества (предельные циклы) семейств автономных нелинейных дискретных систем - Кунцевич, А.В. (Проблемы управления и информатики, 2013)
Для достатньо широкого класу автономних нелінійних дискретних систем визначено умови існування інваріантних множин (стійких граничних циклів). Запропоновано алгоритм визначення інтервальних оцінок зверху для граничних циклів. Алгоритм проілюстровано прикладом. For a rather large family of autonomous nonlinear discrete systems, the conditions for the existence of invariant sets (stable limit cycles) are determined. The algorithm for calculating upper-bound interval estimates for the limit cycles is presented. The algorithm is illustrated with an example.